تقنيات الحجاج اللغوي في رسالة «العهد» من كتاب مجدولين للمنفلوطي - تايب, شمس الهدى; سلطاني, السبتي (University of Eloued جامعة الوادي, 2024)
يحاول المقال الكشف عن طرق اشتغال الآليات اللغوية لتحقق الخطاب الحجاجي اعتمادا على شحنتها الدلالية والتداولية في توجيه المتلقي وجهة مخصوصة، اعتمادا على القرائن اللغوية والمؤشرات الحجاجية الموجهة للحجج التي تشكل تدرج السلالم الحجاجية المنتهية نحو تحقيق مقصدية المتكلم، إضافة إلى ما يستند إليه من مواضع حجاجية تحمل شحنات تسير بالمتلقي نحو ما هو مفترض فعله. يروم هذا البحث الكشف عن فاعلية الأدوات اللغوية وحركيتها الحجاجية في رسالة «العهد» من كتاب ماجدولين للكاتب المصري مصطفى لطفي المنفلوطي، ليتوصل إلى آليات الحجاج اللغوي المعتمدة في الحوار القائم بين الشخصيتين المحوريتين المنخرطتين في الكلام، وتسليم أحدهما بما يوجهه الآخر من كلام. This article attempts to shed light on how linguistic mechanisms operate to achieve the argumentative discourse depending on its semantic and pragmatic context to direct both the interlocutors, the hearer and the speaker for a specific destination. All that is based on the linguistic reasons that direct the arguments to reach a hierarchy of arguments towards achieving the speaker’s intention. Adding to that the argumentative themes used leading the recipient to what he is supposed to do. Therefore, this research aims to investigate the effectiveness of the linguistic techniques and their argumentative dynamics in the treatise of “AL-Ahd” from the book of Magdoline by the Egyptian writer “Mustafa Al-Manfluti”. In order to reach the mechanisms of linguistic arguments adopted in the dialogue between the two pivotal figures involved in the speech, and the recognition of one of them with the guidance of the other from speech.
مقال. مجلة علوم اللغة العربية وآدابها. مج16 . ع.01. جامعة الوادي
Keywords: الحجاج; المؤشرات الحجاجية; السلالم الحجاجية; المواضع; الروابط الحجاجية